Problems of Medical Diagnosis - Wagner, G.; Tautu, P.; Wolber, U. (Methods of Information in Medicine, 1978)
The present bibliography aims at informing and stimulating researchers when studying the multiple facets of medical diagnosis. The complexity of investigation in this domain can be judged by the fact that papers dealing with medical diagnosis do not appear in medical journals only. Clearly, medical diagnosis is no longer a strictly medical problem. Mathematical and statistical models and analyses must be created and improved before computer programs for diagnostics can be elaborated.